Influence of the cation nature on spectral characteristics of cobalt(II)-nickel(II) phosphates - Antraptseva, Nadia; Filipova, Polina; Podobiy, Olena; Bila, Galina (My University, 2023)
The work was carried out with the aim of studying the influence of the cation nature on the spectral characteristics of cobalt(II)-nickel(II) hydrogenphosphates of the general formula Co1-хNiхHPO4·1.5H2O (0<х≤0.35). Using the methods of Infrared and Raman spectroscopy, it was determined that in the structure of hydrogenphosphates there are two types of crystallographically non-identical water molecules that make up the coordination environment of cations. OH-groups of water molecules formed a hard system of different on strength and orientation of hydrogen bonds between molecules water and anion, also between the different OH-groups on the same molecule of water. The bond of ОН-groups of phosphate tetrahedron is more labile. The influence of the cation nature on the asymmetry of the molecules of coordinated water, on the energy H-bonds, bonds MІІ – O (OH2) and P – OH were estimated. It was found that, impact of these bonds weaken with increasing content of nickel(II) in composition of the hydrogenphosphates. Asymmetry of water molecules also decreased, while the bonds O – H coordinating water intensified with an increase a content of nickel(II) in composition of Co1-хNiхHPO4·1.5H2O. HOH angle formed independent OH-groups of the water molecules is not changes. Робота виконана з метою вивчення впливу природи катіонів на спектральні характеристики гідрофосфатів кобальту(ІІ) на спектральні характеристики кобальт(ІІ)-нікель(ІІ) гідрогенфосфатів загальної формули Co1-хNiхHPO4·1.5H2O (0<х≤0.35). Методами ІЧ- та КР-спектроскопії було встановлено, що в структурі гідрогенфосфатів присутні два типи кристалографічно неідентичних молекул води, які складають координаційне оточення катіонів. OH-групи молекул води молекул води утворюють жорстку систему різних за міцністю та орієнтацією водневих зв'язків між молекулами води та аніоном, а також між різними ОН-групами в одній молекулі води. Зв'язок ОН-груп фосфатного тетраедра є більш лабільним. Вплив природи катіона на асиметрію молекул координованої води, на енергію Н-зв'язків, зв'язків MІІ - O (OH2) та P - OH. Встановлено, що вплив цих зв'язків послаблюється зі збільшенням вмісту нікелю(ІІ) у складі гідрогенфосфатів слабшає. Асиметрія молекул води також зменшується, тоді як зв'язки O - H, що координують воду, посилюються зі збільшенням вмісту нікелю(II) у складі гідрогенфосфатів. нікелю(II) у складі Co1-хNiхHPO4-1.5H2O. Кут HOH, утворений самостійними OH-групами молекул води не змінюється.
Keywords: кафедра технології жирів, хімічних технологій харчових добавок та косметичних засобів; hydrogenphosphates; hydrogen bond; cation nature; vibrational spectroscopy; гідрогенфосфати; природа катіонів; коливальна спектроскопія; водневий зв'язок